Molecular palaeontology illuminates the evolution of ecdysozoan vision. Issue 1892 (5th December 2018) - Fleming, James F.; Kristensen, Reinhardt Møbjerg; Sørensen, Martin Vinther; Park, Tae-Yoon S.; Arakawa, Kazuharu; Blaxter, Mark; Rebecchi, Lorena; Guidetti, Roberto; Williams, Tom A.; Roberts, Nicholas W.; Vinther, Jakob; Pisani, Davide
Abstract : Colour vision is known to have arisen only twice—once in Vertebrata and once within the Ecdysozoa, in Arthropoda. However, the evolutionary history of ecdysozoan vision is unclear. At the molecular level, visual pigments, composed of a chromophore and a protein belonging to the opsin family, have different spectral sensitivities and these mediate colour vision. At the morphological level, ecdysozoan vision is conveyed by eyes of variable levels of complexity; from the simple ocelli observed in the velvet worms (phylum Onychophora) to the marvellously complex eyes of insects, spiders, and crustaceans. Here, we explore the evolution of ecdysozoan vision at both the molecular and morphological level; combining analysis of a large-scale opsin dataset that includes previously unknown ecdysozoan opsins with morphological analyses of key Cambrian fossils with preserved eye structures. We found that while several non-arthropod ecdysozoan lineages have multiple opsins, arthropod multi-opsin vision evolved through a series of gene duplications that were fixed in a period of 35–71 million years (Ma) along the stem arthropod lineage. Our integrative study of the fossil and molecular record of vision indicates that fossils with more complex eyes were likely to have possessed a larger complement of opsin genes.